2011
DOI: 10.1111/j.1939-1676.2010.0672.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Furosemide on Left Atrial Pressure in Dogs with Mitral Valve Regurgitation

Abstract: Background: The effects of furosemide on left atrial pressure (LAP) in dogs with mitral regurgitation (MR) have not been documented in a quantitative manner and between different routes of administration.Objective: To document LAP and echocardiographic parameters in MR dogs administered furosemide IV or PO, in order to document changes in LAP after furosemide treatment.Animals: Five healthy Beagle dogs (3 males and 2 females; aged 2 years) were used. Methods: Experimental, cross-over, and interventional study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 27 publications
2
19
1
Order By: Relevance
“…In this study, LAP was significantly decreased by administration of 5 and 10 mg/kg sr‐ISDN. Compared with our previous study, the effect of high‐dose sr‐ISDN on reducing the maximum values of LAP was nearly equal to that of diuretic . This result suggests that high dose of sr‐ISDN has a significant effect on LAP.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…In this study, LAP was significantly decreased by administration of 5 and 10 mg/kg sr‐ISDN. Compared with our previous study, the effect of high‐dose sr‐ISDN on reducing the maximum values of LAP was nearly equal to that of diuretic . This result suggests that high dose of sr‐ISDN has a significant effect on LAP.…”
Section: Discussioncontrasting
confidence: 66%
“…The dogs underwent a surgical procedure to induce MR, and a transmitter catheter was implanted in the left atrium. The surgical procedure and postoperative care were conducted according to our previous report . Thoracic radiography and echocardiography were performed to evaluate pulmonary venous congestion and cardiac dilatation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other echocardiographic parameters did not change significantly. We previously have reported that E wave and E/Ea can be used for the evaluation of preload after administration of high doses of furosemide, and have monitored the reduction of LAP in the short-term [16]. However, present study suggests that it is difficult to evaluate the reduction of LAP after administration of amlodipine by using E wave and E/Ea.…”
Section: Discussionmentioning
confidence: 82%
“…However, there has been few study of the amlodipine in dogs with MR and amlodipine’s effect on LAP has not been fully evaluated in a quantitative manner because of difficulties in directly measuring LAP. We have previously used a radiotelemetry system to report the effects of angiotensin-converting enzyme (ACE) inhibitors and furosemide in dogs with experimentally-induced MR [14-16], and we believe this system would be useful for evaluation of hemodynamic changes after administration of amlodipine.…”
Section: Introductionmentioning
confidence: 99%